1998
DOI: 10.3109/09637489809089407
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cyanogenic glucoside (cyanide) residues in Mbege: an opaque traditional Tanzanian beer

Abstract: Levels of cyanide in two varieties of malted millet, spent grain (Machicha) and opaque beer (Mbege) were determined. Protein content and amino acid composition of the malt, Mbege and Machicha were determined. Mbege was made in the laboratory using an improved method. The cyanide content of millet, malt, spent grain and Mbege were 40.6, 513.4, 18.9 and 8.1 ppm, respectively for the Moshi local millet variety. For Sumbawanga-2 millet variety the cyanide content was found to be 41.2, 489.2, 17.8 and 6.8 ppm for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In other parts of western Kenya, busaa is made from sorghum and chang’aa is made from bananas. Not only does brew type vary within Kenya, but it varies across other African countries including Tanzania, Uganda, and Nigeria, where brew is made from bananas, bamboo, coconut, millet, rice, sorghum, and maize (Mosha et al 1996; Ojiji et al 1993; Shayo et al 1998; World Health Organization 2004). Furthermore, Kenyan residents have told us that reporting brew consumed by amount of money spent is common in other parts of the country as well.…”
Section: Discussionmentioning
confidence: 99%
“…In other parts of western Kenya, busaa is made from sorghum and chang’aa is made from bananas. Not only does brew type vary within Kenya, but it varies across other African countries including Tanzania, Uganda, and Nigeria, where brew is made from bananas, bamboo, coconut, millet, rice, sorghum, and maize (Mosha et al 1996; Ojiji et al 1993; Shayo et al 1998; World Health Organization 2004). Furthermore, Kenyan residents have told us that reporting brew consumed by amount of money spent is common in other parts of the country as well.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively, the content of hydrogen cyanide in the un-germinated samples were quite low ranging between 11.7 to 14.7 ppm as opposed to that of germinated samples 2 days at 23 o C, which was quite high ranging from 141.3 to 163.4 ppm. Surprisingly, Shayo et al (1998) found cyanide content of 513.4 and 489.2 ppm in finger millet malt from Moshi and Sumbawanga varieties. Regarding the kidney beans, similar results were found by Adeparusi (2001) who reported significant reduction on levels of cyanide in Lima beans (Phaseolus lunatus) after soaking autoclaving and toasting.…”
Section: Discussionmentioning
confidence: 86%
“…Steeping of grains (cereals and legumes) in water followed by germination or sprouting is a common household practice in developing countries including Tanzania (Shayo et al, 1998). Germination reduces the high viscosity and water-binding characteristic of starch based porridges.…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 2, it can be seen that animals fed GT showed the highest and most continuous increase in weight over the experimental period. Some of the limiting amino acids such as lysine in cereals (Shayo et al, 1998) are known to be synthesised during germination. Generally, for the two varieties, rats fed germinated feeds performed best.…”
Section: Growth Ratementioning
confidence: 99%